Case report of Fanconi syndrome in Wilms tumor - Ayu Hutami Syarif; Edward Usfie Harahap; Mururul Aisyi (Indonesian Pediatric Society, 2020)
Fanconi syndrome is a group of clinical manifestations including aminoaciduria, proteinuria, glycosuria, hypophosphatemia, and metabolic acidosis. It may occur after exposure to certain drugs. The most common causes are antiepileptic, antiviral, antibiotic, and antineoplastic drugs.1 The two most common causes in the antineoplastic regimen are cisplatin and ifosfamide. Ifosfamide, a derivative of cyclophosphamide, has been used to treat pediatric solid tumors.2 Its high efficacy in numerous studies has led to its long-term administration for pediatric malignancies, including Wilms tumor. Along with other treatment modalities, ifosfamide considerably improved the survival rate (90%) of Wilms tumor while only a few cases resulted in Fanconi syndrome.1,3,4 Here we illustrate a case of presumed drug induced Fanconi syndrome in a Wilms tumor patient who previously achieved remission for 10 months.